Basque Ethnic Identity and Collective Empowerment: Two Key Factors in Well-Being and Community Participation - Zabala, Jon; Conejero, Susana; Pascual, Aitziber; Alonso-Arbiol, Itziar; Amutio, Alberto; Torres-Gomez, Barbara; Padoan De Luca, Sonia; Telletxea, Saioa (Frontiers in Psychology, 2020)
Social identity is a factor that is associated with well-being and community participation. Some studies have shown that ethnic identity goes along with empowerment, and that interaction between the two leads to greater indices of well-being and community participation. However, other works suggest a contextual circumstance (i.e., perceiving one’s own group as a minority and/or being discriminated) may condition the nature of these relations. By means of a cross-sectional study, we analyzed the relations of social identification (or identity fusion) and collective psychological empowerment with personal well-being, social well-being and community participation in a sample of Basques. A total of 748 Basques participated (63.1% women; age M = 39.28; SD = 12.13). Individuals who were highly identified or fused with Basque speakers and who were highly empowered showed higher indices of well-being (both personal and social) and of community participation than non-fused individuals with low empowerment. The results also suggest that social identification (or identity fusion) offsets the negative effects of perceiving the group as a linguistic minority. Collective psychological empowerment proved to be an especially relevant factor that needs to continue to be explored.